UTILIZATION OF POSTER AS A LEARNING MEDIA IN INSTAGRAM AS INFORMATION MEDIA ABOUT TYPES OF NARCOTICS - Nina Riana Harahap; Yenni Triana Lumban Gaol (UNIVERSITAS NEGERI MEDAN, 2020)
Drug abuse in Indonesia has reached a dire state and has become a serious problem, so there is a need for efforts to prevent drug abuse. One of the triggers for the increasing level of drug abuse is the lack of socialization to the public which results in the lack of information obtained by the public regarding the types of narcotics and the dangers of narcotics abuse. The purpose of this study was to determine the function of posters on Instagram social media in making it easier for the public to obtain information related to types of narcotics. The instrument used is a poster, using social media Instagram. The method used in data collection is primary data which is obtained directly through suggestions and comments from followers. The results obtained are the easier it is for the public to obtain information about drugs as a solution in preventing drug abuse. It is hoped that the use of posters on Instagram social media can become a medium of information about the types of narcotics